Maria Magdalena i Provence: Tribal og post-aksial askese - Jensen, Hans Jørgen Lundager (Religionsvidenskabeligt Tidsskrift, 2021)
The final episode in the legend of Mary Magdalene according to Legenda aurea is an example of extreme asceticism in a ‘historic (post-axial) religion’. But the scenario with the saint in the ‘desert’ is built on mythical and ritual themes well-known from ‘tribal’ and ‘archaic’ religions. Axaial asceticism contains a previously unknown, universal ideal about a durative, lifelong asceticism; but this ideal both prolongs and inverts forms of asceticism that were well-known in earlier forms of religion.